DOI: 10.25148/etd.fi14060165
|View full text |Cite
|
Sign up to set email alerts
|

A study of adults' orientations to learning at the national open university of Taiwan

Abstract: Lifelogging has gained more attention due to its wide applications, such as personalized recommendations or memory assistance. The issues of collecting and extracting personal life events have emerged. People often share their life experiences with others through conversations. However, extracting life events from conversations is rarely explored. In this paper, we present Life Event Dialog, a dataset containing fine-grained life event annotations on conversational data. In addition, we initiate a novel conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 271 publications
(498 reference statements)
2
28
1
Order By: Relevance
“…In addition, Chen 4 classified the safety factors into three major components, including personnel safety, cargo safety and machinery safety. Shang and Tseng 19 investigated risk management’s effect to the Kaohsiung port’s safety handling operation.…”
Section: Literature Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Chen 4 classified the safety factors into three major components, including personnel safety, cargo safety and machinery safety. Shang and Tseng 19 investigated risk management’s effect to the Kaohsiung port’s safety handling operation.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Because SOA and CSA involve frequent container operations with heavy machinery, accidents occur quite often, causing financial losses, injuries and even deaths. Chen’s 4 study on accidents of container operations showed that 72% of these accidents were caused by human error. A survey investigated by Shyu et al 5 also showed that 25% of the accidents took place on the container wharf and operation areas, and most of them were due to human error.…”
Section: Introductionmentioning
confidence: 99%
“…These problems highlight the difficulty of using the benefits of digital teaching materials and the impossibility of providing teaching content. Chen (2011) highlighted that up to date, many digital textbooks, of which layout, interface, and broadcast speed were still traditional and unidirectional learning functions. Tang (2012) conducted a content analysis on 30 online Chinese language materials and found that most of the materials provided learners with exercises of listening, speaking, reading, and writing, but most of them were copied from paper books and transferred to webpages without bidirectional and interactive learning functions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Taiwan's declining forest was perceived by students to be a serious sustainability problem. In the 1940s, about 66% of the island was covered by forest (Chen, 1950). In 1977, forest covered only 52% of the island, a decrease of 14% in less than forty years (Taiwan 2000Study, 1989.…”
Section: Resource Sustainabilitymentioning
confidence: 99%